Influence of parental employment status on Dutch and Slovak adolescents' health - Salonna Ferdinand; van Dijk Jitse P; Madarasova Geckova Andrea; Tuinstra Jolanda; Sleskova Maria; Groothoff Johan W; Reijneveld Sijmen A (BMC, 2006)
Abstract Background Recent research shows the possibility that the link between parental employment status and children's health can be affected by different cultural or societal settings. The aim of this study was to explore whether the effect of father's and mother's employment status on several aspects of adolescents' health differs between Slovakia and the Netherlands. Methods Two data sets were used: 2616 Slovak adolescents (mean age 14.9) and 2054 Dutch adolescents (mean age 16.3). Self-rated health, GHQ-12, long-term well-being and Rosenberg self-esteem scale were used to assess the health of adolescents. Parental employment status was classified into the following categories: employed, unemployed, disabled, housewife (among mothers only). Logistic regression analyses were done separately for males and females. Results Results indicate that having an unemployed father negatively influences self-rated health and long-term well-being of Slovak male adolescents, but has no effect on the health of Dutch adolescents. Secondly, having a disabled father has a negative effect on the psychological well-being of Dutch males and the self-rated health of females, but does not influence the health of Slovak adolescents. Thirdly, having a mother who is disabled, unemployed or a housewife has a negative effect on the self-esteem of Slovak adolescents. Fourthly, Dutch males whose mother was a housewife had worse long-term well-being than those with an unemployed mother, whereas Dutch females whose mother was a housewife reported better psychological well-being than those with an employed mother. Conclusion To conclude briefly our results, father's unemployment seems to be a better predictor of health for Slovak adolescents, father's disablement of health for Dutch ones. Mother's employment status seemed to be important for the self-esteem of Slovak adolescents and mother as a housewife for the health of Dutch ones. This suggests that the link between parental employment status and the health of their children may vary between countries, and therefore further studies involving various cultures are needed.